The Scientific Connotation of Historical Materialism and Its Practice and Development in the Context of the New Era - Hu Zhuanxiong; Li Chen; Li Qi (SHS Web of Conferences, 2023)
This article analyzes the important thought proposed by Marx at the watershed of the history of human philosophical thought in the 19th century by studying the materiality, regularity, and developmental nature of the materialist view of history. At the same time, based on several main laws of historical materialism, the essence of the historical development of human society under the basis of material production practice activities was explored. While fully demonstrating the important position of materialism as a Marxist scientific worldview and methodology, it also briefly discusses its innovation and development in the current context of socialism with Chinese characteristics in the new era, providing important reference for scholars to grasp the objective factors and the regularity issues presented in the development of human social history.